2006
DOI: 10.1071/wr06029
|View full text |Cite
|
Sign up to set email alerts
|

Movements of frugivorous birds among fragmented rainforests in the Northern Territory, Australia

Abstract: Rainforests in the Northern Territory occur as small patches, and the frugivorous birds that depend on them are thought to move among the patches. I attached radio-transmitters to 41 birds of four species captured in several locations near Darwin. I recorded 55 interpatch flights, and estimated flight rates as between once per day and five days for figbirds and pied imperial-pigeons. The flight rates for rose-crowned fruit-doves and yellow orioles were much lower, but no reliable estimate could be made. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Panetta and Sparkes 2001). Although birds transport seeds over long distances (Price 2006;Weir and Corlett 2007), most seeds tend to fall within 25 m of the parent plant (Wenny 2000) and dispersal beyond 60 m is rare (Clark et al 2005). Like previous studies, our results showed a significant decrease in seed rain within less than 50 m of a seed source.…”
Section: Shrub Regrowthsupporting
confidence: 45%
“…Panetta and Sparkes 2001). Although birds transport seeds over long distances (Price 2006;Weir and Corlett 2007), most seeds tend to fall within 25 m of the parent plant (Wenny 2000) and dispersal beyond 60 m is rare (Clark et al 2005). Like previous studies, our results showed a significant decrease in seed rain within less than 50 m of a seed source.…”
Section: Shrub Regrowthsupporting
confidence: 45%
“…Several studies demonstrate that large fruit‐eating bird species such as hornbills in South‐East Asia and Africa, and toucans in the Neotropics are able to fly between forest patches of fragmented landscapes and have the potential to act as long‐distance seed dispersers (Kemp ; Powell & Bjork ; Holbrook & Smith ; Graham ; Chaves‐Campos, Arevalo & Araya ; Price ; Kays et al . ; Lenz et al .…”
Section: Introductionmentioning
confidence: 99%
“…In Kakadu National Park, for example, the abundance of figbirds was found to be associated closely with availability of fruit (Woinarski 1993). In another Northern Territory study, Figbirds undertook inter-patch flights as far as 10.5 km with most of these movements occurring after the fruit resource had been exhausted in the original patch (Price 2006). Their reliance on widely distributed and temporary food resources could pre-adapt frugivores to respond to localized storm-induced food shortages through emigration ).…”
Section: Discussionmentioning
confidence: 92%